Role of modified biophysical profile and cerebroplacental ratio in fetal outcome in low risk and high risk pregnancies - ., Urvashi; B. K., Sujani; Sushma, Krishna Sai (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The timely detection of morbid changes in the fetal status followed by adequate interventions to avoid death or disability is one of the most important objectives of prenatal care. Objective of present study was to Comparing the role of modified biophysical profile and the cerebroplacental ratio in fetal outcome in low risk and high risk pregnancies. Methods: Two hundred and seventy three singleton pregnant women were included in this study. Following routine examination, amniotic fluid index, pulsatility index of middle cerebral artery and pulsatility index of umbilical artery, uterine artery mean pulsatility index were evaluated. Non stress test (NST) was done. Modified biophysical profile (MBPP) and Cerebroplacental ratio (CPR in percentile) was generated. Caeserean section because of Fetal distress, birth weight <10th centile, 5min APGAR <7, NICU stay >24hours were used in evaluating the perinatal outcome. Results: Out of 273 cases, 107 cases had poor perinatal outcome. Out of 107 cases, 35.5% cases were IUGR, 39.2% cases underwent caesarean section in view of fetal distress, 39.2% babies had 5min APGAR <7 and 32.7% babies had stayed in NICU for >24hrs. In high risk cases, poor perinatal outcome was seen in 45.5% pregnancies and 36.7% in low risk pregnancies. Sixty seven percent of these cases had abnormal modified biophysical profile and only 7.4% cases had cerebroplacental ratio <1. Conclusions: Modified biophysical profile was proved to be more significant than cerebroplacental ratio in prediction of perinatal outcome.